2004
DOI: 10.1016/j.nucmedbio.2004.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Experiment assessment of mass effects in the rat: implications for small animal PET imaging

Abstract: In vivo imaging using positron emission tomography (PET) is important in the development of new radiopharmaceuticals in rodent animal models for use as biochemical probes, diagnostic agents, or in drug development. We have shown mathematically that, if small animal imaging studies in rodents are to have the same "quality" as human PET studies, the same number of coincidence events must be detected from a typical rodent imaging "voxel" as from the human imaging voxel. To achieve this using the same specifi acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 22 publications
1
61
0
3
Order By: Relevance
“…It has been previously observed that tumor uptake of DOTATOC is influenced by the total amount of administered peptide which depends on receptor occupancy (de Jong et al 1999, Müller et al 2007. Such mass effects are often more relevant in receptor targeted drugs compared with metabolized drugs (Jagoda et al 2004). Unfortunately, the risk of receptor saturation increases when the agent is delivered directly into the arterial supply of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously observed that tumor uptake of DOTATOC is influenced by the total amount of administered peptide which depends on receptor occupancy (de Jong et al 1999, Müller et al 2007. Such mass effects are often more relevant in receptor targeted drugs compared with metabolized drugs (Jagoda et al 2004). Unfortunately, the risk of receptor saturation increases when the agent is delivered directly into the arterial supply of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Tomographic images were reconstructed using a 3D subset expectation maximization algorithm (3D-OSEM) (20 iterations, 5 subsets), which results in a spatial resolution of 1.65 mm full-width at half-maximum (FWHM) isotropic. The usefulness of this piPET imaging device has been previously reported (Jagoda et al, 2004).…”
Section: Apparatusmentioning
confidence: 91%
“…The energy window was 300 650 keV, and decay and dead time corrections were applied. The usefulness of the piPET imaging device has been reported elsewhere [17].…”
Section: Fdg-pet Studymentioning
confidence: 99%